Pedagogical Approaches and Work Performance of Teachers in Public Elementary Schools - Dilidili , Analiza (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the pedagogical approaches and work performance of teachers in public elementary schools in Teresa District during the School Year 2024–2025. Specifically, it identified the extent to which constructivist, inquiry-based, reflective, collaborative, and integrative approaches were utilized and determined their relationship with teachers’ work performance. A descriptive survey research design complemented by documentary analysis was employed. The respondents consisted of 268 teachers from seven public elementary schools, selected through total population sampling. Data on pedagogical approaches were gathered using a researcher-made questionnaire-checklist, while work performance was measured through the teachers’ Individual Performance Commitment and Review (IPCR) results.Findings revealed that the majority of teacher-respondents were middle-aged, predominantly female, married, and holders of a baccalaureate degree, with 5–9 years of teaching experience and occupying Teacher I positions. They had participated in various in-service trainings. The results further showed that pedagogical approaches were “often utilized” across all five domains. Statistical analysis indicated no significant differences in the extent of pedagogical approaches when grouped according to demographic variables. Moreover, teachers demonstrated a “very satisfactory” level of work performance based on their IPCR ratings. Notably, no significant relationship was found between pedagogical approaches and work performance.The study concluded that teachers’ demographic characteristics do not significantly influence their pedagogical practices, and the use of varied pedagogical approaches does not directly correlate with their work performance. It is recommended that school administrators promote the integration of technology, foster collaborative learning environments, and support differentiated instruction. Teachers are encouraged to continuously apply effective pedagogical strategies to enhance student engagement and learning outcomes. The proposed action plan may be implemented, and future studies may explore additional variables.